Organization of a Neurointensive Care Unit - Chavali, Siddharth; Sidiqqi, Obaid A.; Rath, Girija P. (Journal of Neuroanaesthesiology and Critical Care, 2019)
Although in its infancy as a specialty, neurocritical care is rapidly developing its own niche, with a wide profile of patients—both neurosurgical and those with neurological pathologies. Rapid advances in monitoring technology as well as surgical techniques have led to an increasing number of patients, often presenting with myriad concurrent illnesses, who could be best served if managed by specialist neurointensivists. Neurocritical care units are being developed as free-standing intensive care units in several tertiary care hospitals, and literature regarding their establishment and organization is scant, leading to questions regarding how best to utilize resources to gain maximum benefit. This review aims to outline the challenges that are likely to be faced during establishment of such a unit, and to identify certain issues that are specific to this specialty.
Keywords: neurointensive care; organization; neurosurgery; neurology